MENINGKATKAN KEMAMPUAN PRAKTIK POLA RITME DENGAN INSTRUMEN MUSIK NONKONVENSIONAL KELAS VIII SMP NEGERI 9 PONTIANAK - Ramadhan, Syahrul Aditya; Mering, Aloysius; Ramdani, Deden (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study was motivated by the concern about the lack of students? ability in learning music, especially skills in playing musical instrument. One of the possible reason is due to the lack of talent and interest towards music class. The research questions were: (1) Howis learning rhythm pattern through non-conventional percussion instruments for eight-grade students of SMPN 9 Pontianak planned? (2) How is learning rhythm pattern through non-conventional percussion instruments carried out? (3) How does the application of rhythm-pattern lesson using non-conventional percussion instruments improve students? ability in music?.The methodology employed in this study was qualitative method using classroom action research. This is evidenced by (1) the observation notes in the cycle I, II, and III, (2) the improvement of the percentage of students? understanding and ability that rises from 25% (categorised as low) in pre-cycle to 30% (medium category) in cycle I. Thus, a significant upsurgeis observed in cycle II and III which is categorised as high, accounting 50% and 90% respectively.In the pedagogical implication, teacher should use non-conventional percussion instruments to attract learners? motivation in learning as well as to create a positive classroom atmosphere.Key words: Rhythm Pattern, Non-conventional Percussion Instrument.